A functional enzymatic assay as potential readout for a clinical trial of a schistosomiasis vaccine - Kifle, Desalegn W.; Balkhi, Mumtaz Y.; Ono, Yasuko; Davis, Jenn; Doi, Naoko; Arya, Aryandra; Kim, Jiho; Kalyanasundaram, Aravindan; Nandy, Sourav; Rakotozandrindrainy, Njariharinjakamampionona; Staker, Bart; Craig, Justin; et al. (npj vaccines, 2025)
An estimated 200 million people are currently infected with schistosomiasis and an additional 800 million reside in high transmission-risk areas in 78 endemic countries. In this report we describe a functional enzymatic assay based on the core calpain antigen (Sm-p80) of the schistosomiasis vaccine, SchistoShield®. A 44 kDa soluble variant of the core Sm-p80 antigen (B7), was assessed for its enzymatic activity using a fluorescent synthetic substrate. Inhibition of the B7 enzymatic activity by Sm-p80-specific antibodies obtained from pre-clinical trials in rodents, non-human primates as well as from participants of the human clinical trials was measured. The B7 enzyme activity followed a Michaelis-Menten-like kinetic behavior. Statistically significant inhibition of the B7 activity was observed by Sm-p80-specific antibodies produced by immunized mice, non-human primates and humans. This quantitative serological assay could be of value in assessing the effectiveness of the SchistoShield® vaccine in human trials in Africa.